Comparison of postoperative morbidity between piezoelectric surgery and conventional rotary instruments in mandibular third molar surgery: a split-mouth clinical study - Gulnahar, Yakup (Med Oral Patol Oral Cir Bucal, 2021)
BACKGROUND: The extraction of impacted third molar teeth is a common procedure in maxillofacial surgery. The aim of this study was to compare of piezoelectric surgical technique with the one with conventional rotary instruments in terms of edema, trismus and pain, in mandibular third molar surgery. MATERIAL AND METHODS: 20 individuals with symmetrically impacted lower mandibular third molars and 40 teeth were included in the study. Third molars on the left side of each patient were removed with piezosurgery, while the counterparts on the right side were removed with conventional rotary instruments. Postoperatively, the same antibiotic, analgesic, and mouthwash were recommended to both groups. Ultrasound, edema, trismus measurements were performed before surgery, postoperative, postoperative day 2 and postoperative day 7. VAS scale was used to evaluate the pain. RESULTS: The average age of 20 individuals included in the study was found to be 21.85 ± 3.08 years. The operation time of the individuals who underwent the surgery with conventional rotary instruments was found to be 12 minutes 31.70 ± 167.03 seconds, and the operation time in the Piezosurgery group was 19 minutes 10.60 ± 306.59 seconds. There was no significant difference between the two groups in terms of trismus, edema, and pain. CONCLUSIONS: Piezosurgery is a safe method that can be used in molar removal, but in this split-mouth study, it is not found advantageous in terms of postoperative morbidity due to the longer working time compared to the one performed with conventional rotary instruments. Key words:Edema, impacted third molar, pain, piezosurgery, trismus.